Neuromyelitis optica spectrum disorders and pregnancy: therapeutic considerations - Mao-Draayer, Yang; Thiel, Sandra; Mills, Elizabeth A; Chitnis, Tanuja; Fabian, Michelle; Katz Sand, Ilana; Leite, M Isabel; Jarius, Sven; Hellwig, Kerstin (Nature reviews. Neurology, 2020)
Neuromyelitis optica spectrum disorders (NMOSD) are a type of neurological autoimmune disease characterized by attacks of CNS inflammation that are often severe and predominantly affect the spinal cord and optic nerve. The majority of individuals with NMOSD are women, many of whom are of childbearing age. Although NMOSD are rare, several small retrospective studies and case reports have indicated that pregnancy can worsen disease activity and might contribute to disease onset. NMOSD disease activity seems to negatively affect pregnancy outcomes. Moreover, some of the current NMOSD treatments are known to pose risks to the developing fetus and only limited safety data are available for others. Here, we review published studies regarding the relationship between pregnancy outcomes and NMOSD disease activity. We also assess the risks associated with using disease-modifying therapies for NMOSD during the course of pregnancy and breastfeeding. On the basis of the available evidence, we offer recommendations regarding the use of these therapies in the course of pregnancy planning in individuals with NMOSD.